Coated and cutting tools

The coated tool design with a Ti-containing intermediate layer and AlCrSiN/TiSiN coating layers addresses adhesion issues, enhancing wear and oxidation resistance for improved durability.

JP7618814B2Active Publication Date: 2025-01-21KYOCERA CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2023538417
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-07-30
Filing Date
2022-07-12
Publication Date
2025-01-21
Estimated Expiration
2042-07-12

AI Technical Summary

Technical Problem

Existing coated tools face challenges in achieving improved adhesion between the coating layer and the substrate, leading to potential peeling and reduced durability.

Method used

A coated tool design featuring a WC-based cemented carbide base with a coating layer and an intermediate layer containing Ti, and a first coating layer composed of Al, Cr, and Si, with a striped structure to enhance adhesion, and a second coating layer of TiSiN for improved wear resistance and oxidation resistance.

Benefits of technology

The design enhances the adhesion between the coating and substrate, resulting in improved wear resistance, oxidation resistance, and reduced peeling, thereby increasing the durability and performance of the coated tool.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007618814000001
    Figure 0007618814000001
  • Figure 0007618814000002
    Figure 0007618814000002
  • Figure 0007618814000003
    Figure 0007618814000003
Patent Text Reader

Abstract

The coated tool according to the present disclosure has: a base made of a WC-based cemented carbide containing WC particles as a hard phase component and Co as the main component of a binding phase; a coating layer located on the base; and a middle layer located between the base and the coating layer. The middle layer contains Ti, and has an average thickness of 1-15 nm. The coating layer has a first coating layer that is in contact with the middle layer. The first coating layer has: at least one element selected from the group consisting of Al, group 5 elements, group 6 elements, and group 4 elements excluding Ti; at least one element selected from the group consisting of C and N; Si; and Cr.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to coated tools and cutting tools. [Background technology]

[0002] 2. Description of the Related Art As tools used in cutting processes such as turning and milling, coated tools are known in which the surface of a base material such as cemented carbide, cermet, ceramics, etc. is coated with a coating layer to improve wear resistance and the like. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 6773287 [Patent Document 2] Patent No. 4330859 Summary of the Invention

[0004] A coated tool according to one embodiment of the present disclosure has a substrate made of a WC-based cemented carbide containing WC particles as a hard phase component and Co as a main component of a binder phase, a coating layer located on the substrate, and an intermediate layer located between the substrate and the coating layer. The intermediate layer contains Ti and has an average layer thickness of 1 nm or more and 15 nm or less. The coating layer has a first coating layer in contact with the intermediate layer. The first coating layer contains at least one element selected from the group consisting of Al, Group 5 elements, Group 6 elements, and Group 4 elements excluding Ti, at least one element selected from the group consisting of C and N, Si, and Cr. [Brief description of the drawings]

[0005] [Figure 1] FIG. 1 is a perspective view showing an example of a coated tool according to an embodiment. [Diagram 2] FIG. 2 is a side cross-sectional view showing an example of the coated tool 1 according to the embodiment. [Diagram 3] FIG. 3 is a cross-sectional view showing an example of the covering layer 20 according to the embodiment. [Figure 4] FIG. 4 is a schematic enlarged view of a portion H shown in FIG. [Diagram 5] FIG. 5 is a schematic diagram for illustrating the Al content, the Cr content, and the Si content of the first layer and the second layer. [Figure 6] FIG. 6 is a schematic enlarged view of the interface region between the substrate and the first coating layer. [Figure 7] FIG. 7 is a front view showing an example of a cutting tool according to an embodiment. [Figure 8] FIG. 8 is a table summarizing the manufacturing conditions of the coating layers of samples No. 1 to No. 19. [Figure 9] FIG. 9 is a table showing the configurations of the coating layers of samples No. 1 to No. 19. [Figure 10] FIG. 10 is a table summarizing the results of the oxidation test, the wear test, and the peel test for Samples No. 1 to No. 19. [Figure 11] FIG. 11 is a scanning transmission electron microscope image (HAADF-STEM image) of the first coating layer according to the embodiment. [Figure 12] FIG. 12 is a graph showing changes in the Al content, Cr content, Si content and N content in the stacking direction of the first layer and the second layer. [Figure 13] FIG. 13 is a scanning transmission electron microscope image of the coated tool according to the example. [Figure 14] FIG. 14 is a WC mapping image of the coated tool according to the example. [Figure 15] FIG. 15 is a Co mapping image of the coated tool according to the embodiment. [Figure 16] FIG. 16 is a Ti mapping image of the coated tool according to the example. [Figure 17] FIG. 17 is a diagram showing the WC upper extraction range and the Co upper extraction range. [Figure 18] FIG. 18 is a graph showing the measurement results of the Ti content in the extracted range above WC and the extracted range above Co. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0006] Hereinafter, a detailed description will be given of a form for carrying out a coated tool and a cutting tool according to the present disclosure (hereinafter, referred to as an "embodiment") with reference to the drawings. Note that the coated tool and the cutting tool according to the present disclosure are not limited to the embodiment. Moreover, each embodiment can be appropriately combined as long as the processing contents are not contradictory. Moreover, the same parts in each of the following embodiments are given the same reference numerals, and duplicated explanations will be omitted.

[0007] In addition, in the embodiments described below, expressions such as "constant", "orthogonal", "vertical" and "parallel" may be used, but these expressions do not necessarily mean "constant", "orthogonal", "vertical" and "parallel" strictly. In other words, each of the above expressions allows for deviations due to, for example, manufacturing accuracy and installation accuracy.

[0008] The above-mentioned conventional techniques have room for further improvement in terms of improving the adhesion between the coating layer and the substrate.

[0009] <Coated tools> Fig. 1 is a perspective view showing an example of a coated tool according to an embodiment. Fig. 2 is a side cross-sectional view showing an example of a coated tool 1 according to an embodiment. As shown in Fig. 1, the coated tool 1 according to the embodiment has a tip body 2.

[0010] (Chip body 2) Chip body 2 has, for example, a hexahedral shape in which the upper and lower surfaces (surfaces intersecting with the Z-axis shown in FIG. 1) are parallelogram-shaped.

[0011] One corner of the tip body 2 functions as a cutting edge portion. The cutting edge portion has a first surface (e.g., an upper surface) and a second surface (e.g., a side surface) connected to the first surface. In the embodiment, the first surface functions as a "scooping surface" that scoops up chips generated by cutting, and the second surface functions as a "flank surface." A cutting edge is located at least in a part of the ridge where the first surface and the second surface intersect, and the coated tool 1 cuts the workpiece by applying the cutting edge to the workpiece.

[0012] A through hole 5 that vertically passes through the tip body 2 is located in the center of the tip body 2. A screw 75 for attaching the coated tool 1 to a holder 70 (described later) is inserted into the through hole 5 (see FIG. 7).

[0013] As shown in FIG. 2, the chip body 2 has a base 10 and a covering layer 20.

[0014] (Base 10) The substrate 10 is formed of, for example, a cemented carbide. The cemented carbide contains W (tungsten), specifically WC (tungsten carbide). The cemented carbide may also contain Ni (nickel) and / or Co (cobalt). Specifically, the substrate 10 is made of a WC-based cemented carbide containing WC particles as a hard phase component and Co as a main component of a binder phase.

[0015] (Coating layer 20) The coating layer 20 is applied to the substrate 10 for the purpose of improving the wear resistance, heat resistance, etc. of the substrate 10. In the example of FIG. 2, the coating layer 20 covers the entire substrate 10. The coating layer 20 needs to be located at least on the substrate 10. When the coating layer 20 is located on the first surface (here, the upper surface) of the substrate 10, the wear resistance and heat resistance of the first surface are high. When the coating layer 20 is located on the second surface (here, the side surface) of the substrate 10, the wear resistance and heat resistance of the second surface are high.

[0016] Here, a specific configuration of the coating layer 20 will be described with reference to Fig. 3 and Fig. 4. Fig. 3 is a cross-sectional view showing an example of the coating layer 20 according to the embodiment. Fig. 4 is a schematic enlarged view of a portion H shown in Fig. 3.

[0017] As shown in FIG. 3, the coating layer 20 has a first coating layer 23 located on the intermediate layer 22 and a second coating layer 24 located on the first coating layer 23.

[0018] The first coating layer 23 contains at least one element selected from the group consisting of Al, Group 5 elements, Group 6 elements, and Group 4 elements excluding Ti, at least one element selected from the group consisting of C and N, Si, and Cr.

[0019] Specifically, the first coating layer 23 may contain Al, Cr, Si, and N. That is, the first coating layer 23 may be an AlCrSiN layer containing AlCrSiN, which is a nitride of Al, Cr, and Si. Note that the expression "AlCrSiN" means that Al, Cr, Si, and N are present in any ratio, and does not necessarily mean that Al, Cr, Si, and N are present in a 1:1:1:1:1 ratio.

[0020] In this manner, by positioning the first coating layer 23 containing a metal (e.g., Si) contained in the intermediate layer 22 described later on the intermediate layer 22, the adhesion between the intermediate layer 22 and the coating layer 20 is high. This makes it difficult for the coating layer 20 to peel off from the intermediate layer 22, and therefore the durability of the coating layer 20 is high.

[0021] When first coating layer 23 contains Al, Cr, Si and N, the ratio of Al to the metal elements of first coating layer 23 may be 38 atomic % or more and 55 atomic % or less, the ratio of Cr to the metal elements of first coating layer 23 may be 33 atomic % or more and 48 atomic % or less, and the ratio of Si to the metal elements of first coating layer 23 may be 4 atomic % or more and 15 atomic % or less.

[0022] The coated tool 1 having the first coating layer 23 having such a configuration has excellent oxidation resistance.

[0023] 4, the first coating layer 23 has a plurality of first layers 23a and a plurality of second layers 23b. The first coating layer 23 has a striped structure in which the first layers 23a and the second layers 23b are alternately laminated in the thickness direction. The second layers 23b are formed on the first layers 23a.

[0024] The thickness of each of the first layer 23a and the second layer 23b may be 50 nm or less. The first layer 23a and the second layer 23b formed thinly have small residual stress and are less likely to peel off or crack, so that the durability of the coating layer 20 is increased.

[0025] The second coating layer 24 may contain Ti, Si, and N. That is, the second coating layer 24 may be a nitride layer (TiSiN layer) containing Ti and Si. Note that the expression "TiSiN layer" means that Ti, Si, and N are present in any ratio, and does not necessarily mean that Ti, Si, and N are present in a 1:1:1 ratio.

[0026] As a result, for example, when the friction coefficient of the second coating layer 24 is low, the adhesion resistance of the coated tool 1 can be improved. Also, for example, when the hardness of the second coating layer 24 is high, the wear resistance of the coated tool 1 can be improved. Also, for example, when the oxidation onset temperature of the second coating layer 24 is high, the oxidation resistance of the coated tool 1 can be improved.

[0027] The second coating layer 24 may have a striped structure in which at least two layers are located in the thickness direction. Each layer in the striped structure of the second coating layer 24 may contain, for example, Ti, Si, and N. In this case, the Ti content (hereinafter referred to as the "Ti content"), the Si content (hereinafter referred to as the "Si content"), and the N content (hereinafter referred to as the "N content") of the second coating layer 24 may each repeatedly increase and decrease along the thickness direction of the second coating layer 24. Of the metal elements contained in the second coating layer 24, the total of Ti and Si may be 98 atomic % or more. The second coating layer 24 may also have a third layer and a fourth layer alternately located in the thickness direction.

[0028] FIG. 5 is a schematic diagram for illustrating the Al content, the Cr content, and the Si content of the first layer 23a and the second layer 23b.

[0029] The first layer 23a and the second layer 23b contain Al, Cr, Si, and N. Here, the Al content in the first layer 23a is referred to as the first Al content, the Cr content in the first layer 23a is referred to as the first Cr content, and the Si content in the first layer 23a is referred to as the first Si content. The Al content in the second layer 23b is referred to as the second Al content, the Cr content in the second layer 23b is referred to as the second Cr content, and the Si content in the second layer 23b is referred to as the second Si content.

[0030] In this case, the first Al content may be greater than the second Al content, the first Cr content may be less than the second Cr content, and the first Si content may be greater than the second Si content.

[0031] The coated tool 1 having the first coating layer 23 having such a configuration has high hardness and excellent chipping resistance.

[0032] Furthermore, the difference between the Al content of the first layer 23a and the Al content of the second layer 23b may be not less than 1 atomic % and not more than 9 atomic %, the difference between the Cr content of the first layer 23a and the Cr content of the second layer 23b may be not less than 1 atomic % and not more than 12 atomic %, and the difference between the Si content of the first layer 23a and the Si content of the second layer 23b may be not less than 0.5 atomic % and not more than 5 atomic %.

[0033] The coated tool 1 having the first coating layer 23 having such a configuration maintains high oxidation resistance and high hardness, while relieving stress inside the coating and providing excellent wear resistance.

[0034] (Method of manufacturing the coating layer) The coating layer may be formed by, for example, a physical vapor deposition method. Examples of the physical vapor deposition method include an ion plating method and a sputtering method. As an example, when the coating layer is formed by an ion plating method, the coating layer can be formed by the following method.

[0035] First, an example of a method for producing the first coating layer by an ion plating method will be described. First, as an example, metal targets of Cr, Si and Al, or composite alloy targets, or sintered compact targets are prepared.

[0036] Next, the above target, which is the metal source, is evaporated and ionized by arc discharge or glow discharge. The ionized metal is reacted with nitrogen (N2) gas, which is the nitrogen source, and is evaporated onto the surface of the substrate. The above procedure makes it possible to form an AlCrSiN layer.

[0037] In the above procedure, the temperature of the substrate may be set to 500 to 600° C., the nitrogen gas pressure may be set to 1.0 to 6.0 Pa, a DC bias voltage of −50 to −200 V may be applied to the substrate, and the arc discharge current may be set to 100 to 200 A.

[0038] The composition of the first coating layer can be adjusted by independently controlling the voltage and current values ​​during arc discharge and glow discharge applied to the aluminum metal target, the chromium metal target, the aluminum-silicon composite alloy target, and the chromium-silicon composite alloy target for each target. The composition of the coating layer can also be adjusted by controlling the coating time and the atmospheric gas pressure. In one embodiment, the amount of ionization of the target metal can be changed by changing the voltage and current values ​​during arc discharge and glow discharge. The amount of ionization of the target metal can be changed periodically by periodically changing the current value during arc discharge and glow discharge for each target. The amount of ionization of the target metal can be changed periodically by periodically changing the current value during arc discharge and glow discharge of the target at 0.01 to 0.5 min. This allows the coating film to have a configuration in which the content ratio of each metal element changes in each period in the thickness direction.

[0039] When carrying out the above procedure, it is possible to produce a first coating layer having a first layer and a second layer by changing the composition of Al, Si, and Cr so that the amounts of Al and Si are smaller and the amount of Cr is larger, and then changing the composition of Al, Si, and Cr so that the amounts of Al and Si are larger and the amount of Cr is smaller.

[0040] Next, an example of a method for producing the second coating layer, which is a TiSiN layer, will be described.

[0041] Like the first coating layer, the second coating layer may also be formed by physical vapor deposition. As an example, a Ti metal target and a Ti-Si composite alloy target are first prepared. Then, the voltage and current values ​​during arc discharge and glow discharge applied to each prepared target are independently controlled for each target, thereby producing a second coating layer having a striped structure.

[0042] In the above procedure, the substrate temperature may be set to 500 to 600° C., the nitrogen gas pressure may be set to 1.0 to 6.0 Pa, a DC bias voltage of −50 to −200 V may be applied to the substrate, the arc discharge current may be set to 100 to 200 A, and the change period of the arc current may be set to 0.01 to 0.5 min.

[0043] (Middle layer 22) An intermediate layer 22 may be located between the substrate 10 and the coating layer 20. Specifically, the intermediate layer 22 contacts the upper surface of the substrate 10 on one side (here, the lower surface) and contacts the lower surface of the coating layer 20 (first coating layer 23) on the other side (here, the upper surface).

[0044] The intermediate layer 22 has higher adhesion to the substrate 10 than the coating layer 20. Examples of metal elements having such properties include Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, Si, Y, and Ti. The intermediate layer 22 contains at least one of the above metal elements. For example, the intermediate layer 22 may contain Ti. Note that Si is a metalloid element, but in this specification, metalloid elements are also included in the metal elements.

[0045] When the intermediate layer 22 contains Ti, the Ti content in the intermediate layer 22 may be 1.5 atomic % or more. For example, the Ti content in the intermediate layer 22 may be 2.0 atomic % or more.

[0046] The intermediate layer 22 may contain metal elements other than the above metal elements (Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, Si, Y, Ti). However, from the viewpoint of adhesion to the substrate 10, the intermediate layer 22 may contain the above metal elements in a total amount of at least 95 atomic % or more. More preferably, the intermediate layer 22 may contain the above metal elements in a total amount of 98 atomic % or more. The proportion of the metal components in the intermediate layer 22 can be determined, for example, by analysis using an EDS (energy dispersive X-ray spectrometer) attached to a STEM (scanning transmission electron microscope).

[0047] In this way, in the coated tool 1 according to the embodiment, the intermediate layer 22, which has higher wettability with the substrate 10 than the coating layer 20, is provided between the substrate 10 and the coating layer 20, thereby improving the adhesion between the substrate 10 and the coating layer 20. Since the intermediate layer 22 also has high adhesion with the coating layer 20, peeling of the coating layer 20 from the intermediate layer 22 is unlikely to occur.

[0048] The thickness of intermediate layer 22 may be, for example, not less than 0.1 nm and less than 20.0 nm.

[0049] Fig. 6 is a schematic enlarged view of the interface region between the substrate 10 and the first coating layer 23. Fig. 6 shows the interface region between the substrate 10 and the first coating layer 23 in a cross section perpendicular to the surface of the substrate 10.

[0050] As shown in FIG. 6, the intermediate layer 22 located in the interface region between the substrate 10 and the first coating layer 23 is located mostly on the WC particles 10a out of the WC particles 10a and binder phase 10b contained in the substrate 10.

[0051] Specifically, the maximum value of Ti (atm%) obtained by elemental analysis in a direction crossing from the first coating layer 23 to the WC particles 10a is defined as the Ti(WC) value, and the maximum value of Ti (atm%) obtained by elemental analysis in a direction crossing from the first coating layer 23 to the WC and binder phase 10b is defined as the Ti(Co) value. The ratio of the Ti(WC) value to the Ti(Co) value (Ti(Co) value / Ti(WC) value) is defined as the Ti(Co / WC) ratio. In this case, the coated tool 1 according to the embodiment has a Ti(Co / WC) ratio of 0.8 or less.

[0052] Conventionally, the first coating layer, which is composed of at least one element selected from the group consisting of Al, Cr, Si, Group 5 elements, Group 6 elements, and Group 4 elements excluding Ti, and at least one element selected from the group consisting of C and N, has room for improvement in adhesion to WC particles. On the other hand, Ti has good adhesion to both the first coating layer and the WC particles. Therefore, as in the coated tool 1 according to the embodiment, by introducing an intermediate layer 22 containing Ti between the first coating layer 23 and the WC particles 10a, the adhesion between the substrate 10 and the first coating layer 23 can be improved.

[0053] The intermediate layer 22 having the above-mentioned configuration can be obtained, for example, by the following manufacturing method.

[0054] (Method of manufacturing intermediate layer) 8×10 -3 ~1×10 -4 The substrate is heated in a reduced pressure environment of 1.0 Pa to a surface temperature of 500 to 600°C. Then, argon gas is introduced as the atmospheric gas, and the pressure is maintained at 3.0 Pa. Next, the bias voltage is set to -400 V, and argon bombardment is performed for 11 minutes. Next, the pressure is reduced to 0.1 Pa, and an arc current of 130 to 160 A is applied to the Ti metal evaporation source, and processing is performed for 0.3 minutes to form a Ti-containing layer as an intermediate layer on the surface of the substrate.

[0055] <Argon bombardment pretreatment condition 1> (1) Bias voltage: -400V (2) Pressure: 3 Pa (3) Processing time: 11 minutes

[0056] <Film formation conditions 1 of Ti-containing layer> (1) Arc current: -100 to -200 A (2) Bias voltage: -380 to -430 V (3) Pressure: 0.1 Pa (4) Processing time: 0.3 minutes

[0057] The Ti-containing layer may contain other metal elements by diffusion, for example. The Ti-containing layer may contain 50 to 95 atomic% of metal elements other than Ti.

[0058] In addition, the adhesion between the bonding phase containing Co and Ti is poor. Therefore, the overall adhesion between the substrate and the coating layer is improved when the amount of Ti located on the bonding phase containing Co is as small as possible. Thus, as in the coating tool 1 according to the embodiment, by adopting a configuration in which more Ti is located on the WC particles 10a among the WC particles 10a and the bonding phase 10b contained in the substrate 10, the adhesion between the substrate 10 and the first coating layer 23 can be improved, and thereby, the wear resistance and chipping resistance of the coating tool 1 can be improved.

[0059] In addition, in a cross-section perpendicular to the surface of the substrate 10, at least a part of the bonding phase 10b may be in contact with the first coating layer 23.

[0060] The adhesion between the first coating layer composed of at least one element selected from the group consisting of Al, Cr, Si, Group 5 elements, Group 6 elements, and Group 4 elements excluding Ti, and the bonding phase containing Co is better than the adhesion between the bonding phase containing Co and Ti. Therefore, when at least a part of the bonding phase 10b is configured to be in contact with the first coating layer 23, the adhesion between the substrate 10 and the first coating layer 23 can be further improved, and the wear resistance and chipping resistance of the coating tool 1 can be further improved.

[0061] The intermediate layer 22 having the above configuration can be manufactured, for example, under the following conditions. <Argon bombardment pretreatment conditions 2> (1) Bias voltage: -400 V (2) Pressure: 3 Pa (3) Processing time: 11 minutes <Film formation conditions 2 of Ti-containing layer> (1) Arc current: 100 - 200 A (2) Bias voltage: -380 to -430 V (3) Pressure: 0.1 Pa (4) Processing time: 0.3 minutes <Post-treatment conditions 2 of argon bombardment> (1) Bias voltage: -200 V (2) Pressure: 3 Pa (3) Processing time: 1 minute Repeat the film formation conditions 2 of the Ti-containing layer and the post-treatment conditions 2 of argon bombardment alternately one or more times.

[0062] Also, in the interface region, the region containing Ti on the WC particles 10a, that is, the thickness of the intermediate layer 22 on the WC particles 10a may be 1 nm or more and 15 nm or less.

[0063] When the thickness of the intermediate layer 22 is 1 nm or more, the adhesion effect between the first coating layer 23 and the WC particles 10a is more effectively exerted. When the thickness of the intermediate layer 22 is 15 nm or less, the occurrence and progression of cracks from the intermediate layer 22 are suppressed. Therefore, by setting the thickness of the intermediate layer 22 on the WC particles 10a to be 1 nm or more and 15 nm or less, the adhesion between the substrate 10 and the first coating layer 23 can be further improved, and the wear resistance and defect resistance of the coated tool 1 can be further improved.

[0064] The intermediate layer 22 having the above configuration can be manufactured, for example, under the following conditions. <Pretreatment conditions 3 of argon bombardment> (1) Bias voltage: -400 V (2) Pressure: 3 Pa or less (3) Processing time: 11 minutes

[0065] <Film formation conditions 3 of Ti-containing layer> (1) Arc current: 100 A to 180 A or less (2) Bias voltage: -400V (3) Pressure: 0.1 Pa (4) Processing time: 0.3 minutes

[0066] <Argon bombardment post-treatment condition 3> (1) Bias voltage: -200V (2) Pressure: 3 Pa (3) Processing time: 1 minute The Ti-containing layer deposition condition 3 and the argon bombardment post-treatment condition 3 are alternately repeated 1 to 20 times.

[0067] <Cutting tools> Next, the configuration of a cutting tool including the above-mentioned coated tool 1 will be described with reference to Fig. 7. Fig. 7 is a front view showing an example of a cutting tool according to an embodiment.

[0068] As shown in FIG. 7, a cutting tool 100 according to the embodiment includes a coated tool 1 and a holder 70 for fixing the coated tool 1.

[0069] The holder 70 is a rod-shaped member extending from a first end (the upper end in FIG. 7) to a second end (the lower end in FIG. 7). The holder 70 is made of, for example, steel or cast iron. Of these materials, it is particularly preferable to use steel, which has high toughness.

[0070] The holder 70 has a pocket 73 at the end on the first end side. The pocket 73 is a portion where the coated tool 1 is attached, and has a seating surface that intersects with the rotation direction of the workpiece and a constraint side surface that is inclined relative to the seating surface. The seating surface is provided with a screw hole into which a screw 75, which will be described later, is screwed.

[0071] The coated tool 1 is positioned in a pocket 73 of the holder 70, and is attached to the holder 70 by a screw 75. That is, the screw 75 is inserted into the through hole 5 of the coated tool 1, and the tip of the screw 75 is inserted into a screw hole formed in the seating surface of the pocket 73 to screw the threaded portions together. In this way, the coated tool 1 is attached to the holder 70 such that the cutting edge portion protrudes outward from the holder 70.

[0072] In the embodiment, a cutting tool used in so-called turning is exemplified. Examples of turning include inner diameter machining, outer diameter machining, and grooving. The cutting tool is not limited to that used in turning. For example, the coated tool 1 may be used as a cutting tool used in turning. Examples of cutting tools used in turning include milling cutters such as flat milling cutters, face milling cutters, side milling cutters, and groove milling cutters, and end mills such as single-blade end mills, multiple-blade end mills, tapered-blade end mills, and ball end mills. EXAMPLES

[0073] Examples of the present disclosure will be specifically described below. Note that the present disclosure is not limited to the examples shown below.

[0074] Samples No. 1 to No. 19 were prepared, each having a coating layer on a substrate made of WC-based cemented carbide, and the presence or absence of a striped structure was confirmed, and the Al content, Cr content, and Si content were measured. The preparation conditions for the intermediate layer in Samples No. 2 to No. 19 are as shown in FIG. 8. Among Samples No. 1 to No. 19, Samples No. 2 to No. 5 and No. 7 to No. 14 correspond to examples of the present disclosure, and Samples No. 1, No. 6, and No. 15 to No. 19 correspond to comparative examples. The "coating time" which is a manufacturing condition for the intermediate layer shown in FIG. 8 corresponds to the "treatment time" in the film formation conditions for the Ti-containing layer described above.

[0075] FIG. 9 is a table showing the configuration of the coating layer of samples No. 1 to No. 19. As shown in FIG. 9, sample No. 1 does not have an intermediate layer between the substrate and the first coating layer. In contrast, samples No. 2 to No. 19 have an intermediate layer between the substrate and the first coating layer. Among them, samples No. 2 to No. 18 have an intermediate layer containing Ti, and sample No. 19 has an intermediate layer containing Cr. The thickness (average thickness) of the intermediate layer of samples No. 2 to No. 19 was 0.1 nm for sample No. 2, 1 nm for sample No. 3, 8 nm for sample No. 4, 15 nm for sample No. 5, 18 nm for sample No. 6, 8 nm for sample No. 7 to No. 14, 5 nm for sample No. 15, 3 nm for sample No. 16, 5 nm for sample No. 17, 10 nm for sample No. 18, and 2 nm for sample No. 19.

[0076] Samples No. 1 to No. 14 have a first coating layer (AlCrSiN layer) containing Al, Cr, Si, and N. The average composition of the AlCrSiN layer of samples No. 1 to No. 14 is (Al 50 Cr 39 S 11 ) N. The first coating layer of these samples had a striped structure in which the first layer and the second layer were alternately positioned.

[0077] The first coating layers of the samples No. 15 to No. 19 did not have a striped structure. The composition of the first coating layers of the samples No. 15 to No. 19 was as follows: Sample No. 15 had (Al 50 Cr 50 )N, sample No. 16 is (Ti 50 Al 50 )N, sample No. 17 is (Ti 50 Al 40 S 10 )N, sample No. 18 is TiN, and sample No. 19 is (Al 55 CTi 25 Cr 15 Si3Y2)N.

[0078] For samples No. 1 to No. 14 having a striped structure, the differences between the Al content in the first layer and the Al content in the second layer (Al content differences) were 6 atomic%, 6 atomic%, 6 atomic%, 6 atomic%, 6 atomic%, 6 atomic%, 2 atomic%, 4 atomic%, 6 atomic%, 8 atomic%, 9 atomic%, 10 atomic%, 9 atomic%, and 6 atomic%, respectively.

[0079] For samples No. 1 to No. 14 having a striped structure, the differences between the Cr content in the first layer and the Cr content in the second layer (Cr content difference) were 8 atomic%, 8 atomic%, 8 atomic%, 8 atomic%, 8 atomic%, 8 atomic%, 3 atomic%, 6 atomic%, 9 atomic%, 12 atomic%, 11 atomic%, 11 atomic%, 13 atomic%, and 12 atomic%, respectively.

[0080] For samples No. 1 to No. 14 having a striped structure, the differences between the Si content in the first layer and the Si content in the second layer (Si content difference) were 2 atomic%, 2 atomic%, 2 atomic%, 2 atomic%, 2 atomic%, 1 atomic%, 2 atomic%, 3 atomic%, 4 atomic%, 2 atomic%, 1 atomic%, 4 atomic%, and 6 atomic%, respectively.

[0081] 10 is a table summarizing the results of the oxidation test, abrasion test, and peel test for Samples No. 1 to No. 19. The test conditions for the oxidation test, abrasion test, and peel test are as follows.

[0082] <Oxidation test> For the AlCr-based coating layers of samples No. 1 to No. 15, a specified intermediate layer was formed on the platinum wire, and then the coating layer was formed to a thickness of 3 μm. The resulting coated platinum wire was then subjected to an oxidation test in which it was held in air at 1000°C for 1 hour.

[0083] The Ti-based coating layers of samples No. 16 to No. 19 were prepared by subjecting platinum wire to a prescribed intermediate layer formation process, then forming a coating layer to a thickness of 3 μm. The resulting coated platinum wires were then subjected to an oxidation test in which they were kept in air at 800°C for 1 hour.

[0084] After the test, the platinum wire was cross-sectionally processed and the thickness of the oxide film was observed by observing the film condition from the cross section. Note that a smaller oxide film thickness is an indicator of better oxidation resistance.

[0085] <Wear test> The wear test was performed using a two-blade carbide ball end mill (model number: 2KMBL0200-0800-S4) under the following conditions. (1) Cutting method: Pocket machining (2) Work material: SKD11H (3) Feed fz: 1320mm / min (4) Cutting depth: ap 0.08mm x ae 0.20mm (5) Evaluation method: The wear width of the side flank after cutting 20m was measured using a microscope.

[0086] <Peel test> The peeling test was carried out using a scratch tester. The load range was 20 to 150 N, and the load at which peeling occurred was used for evaluation.

[0087] Samples No. 2 to No. 5 and No. 7 to No. 14, which had a Ti-containing intermediate layer of 1 nm to 15 nm and at least one element selected from the group consisting of Al, group 4 elements, group 5 elements, and group 6 elements, and Si and Cr, were superior in adhesion to the coating layer compared to samples No. 1 and No. 19, and also exhibited higher wear resistance compared to samples No. 1, No. 6, and No. 15 to No. 19. In particular, samples No. 2 to No. 5 and No. 7 to No. 11, in which the first coating layer had first and second layers alternately positioned in the thickness direction, the difference between the Al content of the first layer and the Al content of the second layer was 1 atomic % to 9 atomic %, the difference between the Cr content of the first layer and the Cr content of the second layer was 1 atomic % to 12 atomic %, and the difference between the Si content of the first layer and the Si content of the second layer was 0.5 atomic % to 5 atomic %, were superior in oxidation resistance and wear resistance.

[0088] <Elemental analysis of the first coating layer> An elemental analysis was performed by EDX analysis on the first coating layer of sample No. 4. Specifically, a range spanning multiple first and second layers was extracted from the EDX analysis data, and the changes in Al content, Cr content, Si content, and N content in the direction along the stacking direction of the first and second layers (scanning direction) for the extracted range were measured. The analysis conditions were as follows: (1) Sample pretreatment: Thin sectioning using FIB method (μ-sampling method) (2) Elemental analysis (area analysis) (3) Scanning transmission electron microscope: JEOL JEM-ARM200F (4)Accelerating voltage: 200 kV (5) Beam diameter: approx. 0.2 nmφ (6) Elemental analyzer: JEOL JED-2300T (7) X-ray detector: Si drift detector (8) Energy resolution: Approximately 140 eV (9) X-ray extraction angle: 21.9° (10) Solid angle: 0.98sr (11) Number of captured pixels: 256 x 256

[0089] 11 is a scanning transmission electron microscope image (HAADF-STEM image) of the first coating layer according to the embodiment. As shown in FIG. 11, it can be seen that the first coating layer according to the example has a striped structure in which the first layer and the second layer are alternately positioned.

[0090] Fig. 12 is a graph showing the changes in Al content, Cr content, Si content and N content in the stacking direction of the first layer and the second layer. The horizontal axis of the graph shown in Fig. 12 corresponds to the scanning direction shown in Fig. 11. That is, the start point of the scanning direction shown in Fig. 11 ("0 nm" in Fig. 11) corresponds to "0 nm" on the horizontal axis of the graph shown in Fig. 12, and the end point of the scanning direction shown in Fig. 11 ("50 nm" in Fig. 11) corresponds to "50 nm" on the horizontal axis of the graph shown in Fig. 12.

[0091] As shown in Fig. 12, it can be seen that the Al content and the Cr content vary periodically along the scanning direction (i.e., the stacking direction of the first and second layers). Specifically, the Al content increases in the first layer and decreases in the second layer. Also, the Cr content decreases in the first layer and increases in the second layer.

[0092] The Si content also varies periodically along the scanning direction. Specifically, the Si content increases in the first layer and decreases in the second layer, similar to the Al content.

[0093] Thus, in the first coating layer of the embodiment, the Al content in the first layer (first Al content) is greater than the Al content in the second layer (second Al content), the first Cr content in the first layer is less than the second Cr content in the second layer, and the first Si content in the first layer is greater than the second Si content in the second layer.

[0094] Furthermore, as shown in FIG. 12, it can be seen that the difference between the first Al content and the second Al content is not less than 1 atomic % and not more than 9 atomic %, the difference between the first Cr content and the second Cr content is not less than 1 atomic % and not more than 12 atomic %, and the difference between the first Si content and the second Si content is not less than 0.5 atomic % and not more than 5 atomic %.

[0095] <Elemental analysis of the interface region between the substrate and the first coating layer> The interface region between the substrate and the first coating layer in the sample manufactured by the above manufacturing method was subjected to elemental analysis by EDX analysis under the same analysis conditions as those for the first coating layer described above.

[0096] Fig. 13 is a scanning transmission electron microscope image of the coated tool according to the example. Specifically, Fig. 13 shows a scanning transmission electron microscope image (HAADF-STEM image) of the interface region between the substrate and the first coating layer in a cross section perpendicular to the surface of the substrate.

[0097] In addition, FIGS. 14 to 16 show elemental mapping images in the same region as the scanning transmission electron microscope image shown in FIG. 13. Specifically, FIG. 14 is a WC mapping image of the coated tool according to the example, FIG. 15 is a Co mapping image of the coated tool according to the example, and FIG. 16 is a Ti mapping image of the coated tool according to the example.

[0098] As shown in FIGS. 14 to 16, in the coated tool according to the example, Ti located in the interface region between the substrate and the first coating layer is mostly located above WC among WC and Co contained in the substrate.

[0099] In addition, as shown in FIG. 15, in the coated tool according to the example, at least a part of the binder phase containing Co is in contact with the first coating layer.

[0100] <Comparison of Ti amounts> For sample No. 2, from the EDX analysis data (surface analysis data), the range on the line crossing from the first coating layer to the WC particles (hereinafter referred to as the "extraction range on WC") and the range on the line crossing from the first coating layer to the binder phase (hereinafter referred to as the "extraction range on Co") were extracted respectively, and the Ti amount was measured for each extraction range. The analysis conditions of the EDX analysis data for extraction are the same as the conditions for the EDX analysis of the first coating layer described above.

[0101] FIG. 17 is a diagram showing the extraction range on WC and the extraction range on Co. As shown in FIG. 17, a region with a length of 50.0 nm along the direction crossing from the first coating layer to the WC particles was defined as the WC extraction range. The starting point (0.0 nm) of the extraction range on WC is located in the first coating layer, and the end point (50.0 nm) is located in the WC particles.

[0102] In addition, a range with a length of 50.0 nm along the direction crossing from the first coating layer to the binder phase containing Co was defined as the extraction range on Co. The starting point (0.0 nm) of the extraction range on Co is located in the first coating layer, and the end point (50.0 nm) is located in the binder phase.

[0103] Fig. 18 is a graph showing the results of measuring the amount of Ti in the area extracted above WC and the area extracted above Co. In Fig. 18, the amount of Ti measured in the area extracted above WC is shown by an open circle, and the amount of Ti measured in the area extracted above Co is shown by a filled circle.

[0104] Here, the maximum value of the Ti amount (atm%) obtained by elemental analysis of the extracted range on WC is defined as the Ti(WC) value, and the maximum value of the Ti amount (atm%) obtained by elemental analysis of the extracted range on Co is defined as the Ti(Co) value. As shown in Fig. 18, the Ti(WC) value was about 2.55 atm%, and the Ti(Co) value was 1.35 atm%. The ratio of the Ti(WC) value to the Ti(Co) value (Ti(Co) value / Ti(WC) value) was about 0.53.

[0105] Thus, in the coated tools according to the examples, the ratio between the Ti(WC) value and the Ti(Co) value (Ti(Co / WC) ratio) is smaller than 0.8.

[0106] As described above, the coated tool according to the embodiment (for example, the coated tool 1) has a substrate (for example, the substrate 10) made of a WC-based cemented carbide containing WC particles (for example, the WC particles 10a) as a hard phase component and Co as a main component of a binder phase (for example, the binder phase 10b), a coating layer (for example, the coating layer 20) located on the substrate, and an intermediate layer (for example, the intermediate layer 22) located between the substrate and the coating layer. The intermediate layer contains Ti and has an average layer thickness of 1 nm or more and 15 nm or less. The coating layer has a first coating layer (for example, the first coating layer 23) in contact with the intermediate layer. The first coating layer contains at least one element selected from the group consisting of Al, Group 5 elements, Group 6 elements, and Group 4 elements excluding Ti, at least one element selected from the group consisting of C, N, Si, and Cr.

[0107] Therefore, according to the coated tool according to the embodiment, the adhesion between the coating layer and the substrate can be improved.

[0108] 1 is merely an example and does not limit the shape of the coated tool according to the present disclosure. The coated tool according to the present disclosure may have, for example, a rod-shaped main body having a rotation axis and extending from a first end to a second end, a cutting edge located at the first end of the main body, and a groove extending spirally from the cutting edge toward the second end of the main body.

[0109] Further advantages and modifications may readily occur to those skilled in the art. Thus, the invention in its broader aspects is not limited to the specific details and representative embodiments shown and described above. Accordingly, various modifications may be made without departing from the spirit or scope of the general inventive concept as defined by the appended claims and equivalents thereof. [Explanation of symbols]

[0110] 1. Coated tools 2 Chip body 5 Through hole 10 Base 10a WC particles 10b Bonded phase 20 Covering layer 22 Middle Class 23 First coating layer 24 Second coating layer 70 Holder 73 Pocket 75 Screw 100 cutting tools

Claims

1. A substrate made of a WC-based cemented carbide containing WC particles as a hard phase component and Co as a main component of a binder phase; a coating layer overlying the substrate; and an intermediate layer located between the substrate and the coating layer; The intermediate layer contains Ti and has an average layer thickness of 1 nm or more and 15 nm or less, The coating layer includes a first coating layer in contact with the intermediate layer, The first coating layer contains at least one element selected from the group consisting of Al, Group 5 elements, Group 6 elements, and Group 4 elements excluding Ti, at least one element selected from the group consisting of C and N, Si, and Cr, The first coating layer has a first layer and a second layer alternately positioned in a thickness direction, the first layer and the second layer contain Al, Cr, Si, and N; A coated tool, wherein the Al content of the first layer is greater than the Al content of the second layer, the Cr content of the first layer is less than the Cr content of the second layer, and the Si content of the first layer is greater than the Si content of the second layer.

2. The first coating layer includes Al, Cr, Si, and N, The ratio of Al to the metal elements of the first coating layer is 38 atomic % or more and 55 atomic % or less, The ratio of Cr to the metal elements of the first coating layer is 33 atomic % or more and 48 atomic % or less, 2. The coated tool according to claim 1, wherein a ratio of Si to the metal elements in the first coating layer is 4 atomic % or more and 15 atomic % or less.

3. a difference between an Al content of the first layer and an Al content of the second layer is 1 atomic % or more and 9 atomic % or less; a difference between the Cr content of the first layer and the Cr content of the second layer is 1 atomic % or more and 12 atomic % or less; 2. The coated tool according to claim 1, wherein a difference between a Si content of the first layer and a Si content of the second layer is 0.5 atomic % or more and 5 atomic % or less.

4. A coated tool as described in claim 1, wherein the intermediate layer is located in a greater amount on top of the WC particles among the WC particles and the binder phase contained in the substrate.

5. a rod-shaped holder having a pocket at one end; The coated tool according to any one of claims 1 to 4, which is located in the pocket. A cutting tool having

Citation Information

Patent Citations

  • Solvent-freee paint composition

    JP1982000171A

  • Drawing reader

    JP1985004366A

  • Coated ultra-high hardness sintered body tool

    JP2003340604A

  • Coating with high abrasion resistance and high hardness

    JP2005042146A

  • Abrasion-resistant hard coating for workpieces and method for manufacturing the same

    JP2010521589A